1998
DOI: 10.1021/jp983114u
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Calculations on α-Substituted Ethyl Cations:  A Comparison between B3LYP and Post-HF Methods

Abstract: Alkyl cations of the form CH3C(+)HR have been investigated using high-level quantum chemical methods to study the influence of α-substituents R (R = H, CH3, CHCH2, C⋮CH, F, and Cl) on cation geometries and relative energies with respect to the neutral precursors CH3CH2R. The results of density-functional B3LYP computations with a variety of basis sets were compared with MP2, MP4, QCISD(T), and CBS-Q model chemistry results and benchmarked against experimental data. The results show that geometrical features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The calculations were carried out over Gaussian 09 package (Frisch et al, 2013). Full geometry optimizations were performed by using the HF method, and RB3LYP functional was selected because it was suitable for discussing the reaction profile (van Alem et al, 1998).…”
Section: Calculationsmentioning
confidence: 99%
“…The calculations were carried out over Gaussian 09 package (Frisch et al, 2013). Full geometry optimizations were performed by using the HF method, and RB3LYP functional was selected because it was suitable for discussing the reaction profile (van Alem et al, 1998).…”
Section: Calculationsmentioning
confidence: 99%
“…Because it involves bond breaking/forming, the bridged cation (1c) needs a priori a higher level of computation than the hyperconjugated system (1a) (van Alem et al, 1998). However, all the correlated levels converged to similar energy differences, within a few kcal/mol.…”
Section: Computational Considerationsmentioning
confidence: 99%
“…Interestingly, a large number of theoretical studies of the ethyl cation and its hyperconjugation effect have been reported, including the classic work done by Pople [40][41][42] and others [43][44][45]. However, Zuilhof et al [46] and Carneiro et al [47] analyzed the molecular geometry of ethyl cation using the MP2(FULL)/6-31G(d,p) and B3LYP/6-311G(d,p) calculations. At these two levels of theory, the structure of the ethyl cation was characterized by a C 2v point group, although two distinct results for the distance between C1 and C2 carbons (see Fig.…”
Section: Optimized Geometrymentioning
confidence: 99%
“…These RC1-C2 distances lie midway between the experimental data of 1.34 and 1.53 Å for ethene (2a) and ethane (2c) [48], respectively. On the basis of these results [49], we have assumed that a C1-C2 bond length of 1.38 Å is an appropriate parameter for evaluating the hyperconjugation effect of the ethyl cation [46][47][48][49].…”
Section: Optimized Geometrymentioning
confidence: 99%